2021
DOI: 10.17159/2309-8775/2021/v63n3a4
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of CHIRPS-based satellite rainfall estimates for South Africa

Abstract: Long-term rainfall data with good spatial and temporal distribution is essential for all climate-related analyses. The availability of observed rainfall data has become increasingly problematic over the years due to a limited and deteriorating rainfall station network, occasioned by limited reporting and/or quality control of rainfall and, in some cases, closure of these stations. Remotely sensed satellite-based rainfall data sets offer an alternative source of information. In this study, daily and monthly rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…This means that, CHIRPS data, aggregated to any spatial scale between 10 × 10 km and 25 × 25 km, can fairly represent the local rainfall conditions in ORTDM. This finding is supported by Duplessis and Kibii [69], who found that monthly CHIRPS data estimated rainfall very well in 46 locations across South Africa, with an average R 2 of 0.60. In the Eastern Cape, Mhalalela et al [70] also found significant correlations ranging between 0.61 and 0.90 between CHIRPS and WS data.…”
Section: Satellite Data For Ibci Designsupporting
confidence: 61%
“…This means that, CHIRPS data, aggregated to any spatial scale between 10 × 10 km and 25 × 25 km, can fairly represent the local rainfall conditions in ORTDM. This finding is supported by Duplessis and Kibii [69], who found that monthly CHIRPS data estimated rainfall very well in 46 locations across South Africa, with an average R 2 of 0.60. In the Eastern Cape, Mhalalela et al [70] also found significant correlations ranging between 0.61 and 0.90 between CHIRPS and WS data.…”
Section: Satellite Data For Ibci Designsupporting
confidence: 61%
“…During summer, the highest temperature is about 30℃, while winter recorded the lowest temperature of 3℃ at night as reported in Chabalala et al [21]. In comparison to South Africa's average annual rainfall of 450 mm [22], this study area receives an average of 700 mm per year. The study area receives high average monthly rainfall during the summer months (December to February), and low average monthly rainfall during the winter months (June to August).…”
Section: Study Areasupporting
confidence: 49%
“…For instance, Bichet and Diedhiou (2018a, 2018b) in their study on precipitation extremes found a good performance of CHIRPS datasets in the representation of mean precipitation, intensity of precipitation, number of wet days and average length of dry spell when compared with 18 daily rainfall observing stations across the the Sahel and Guinea coast of West Africa. Also, the performance of CHIRPS over Africa (Maidment et al, 2015), and in particular the subregions of focus (i.e., Eastern Africa (Dinku et al, 2018), Western Africa (Sacré Regis et al, 2020), Southern Africa (du Plessis & Kibii, 2021) and Central Africa (Camberlin et al, 2019)) shows a good agreement with other sources of observational data as well as gauge measurement. It is, therefore, suitable for drought monitoring and analysis.…”
Section: Methodsmentioning
confidence: 69%